Comprehensive strategies in breast cancer-related lymphedema prevention: insights from a multifaceted program - Bhimani, Fardeen; McEvoy, Maureen; Chen, Yu; Gupta, Anjuli; Pastoriza, Jessica; Cavalli, Arianna; Obaid, Liane; Rachofsky, Carolyn; Fruchter, Shani; Feldman, Sheldon (Frontiers in Oncology, 2024)
Background: Breast cancer-related lymphedema (BCRL) profoundly impacts patients' quality of life, causing heightened depression, anxiety, and physical limitations. Surgical removal of the axillary nodes, combined with radiation therapy, is a significant risk factor for BCRL. Smarter axillary surgery, coupled with early detection and fostering lymphedema education, significantly improves BCRL management, promoting timely diagnosis and treatment. A lymphedema prevention program encompassing all these factors can significantly aid in preventing, treating, and reducing the severity of BCRL cases. Therefore, our study aims to share our insights and experiences gained from implementing a lymphedema prevention program at our institution.Methods & Results: At our institution, axillary reverse mapping (ARM) is performed on all patients undergoing axillary surgery. We surveil these patients with pre-and postoperative SOZO ® measurements using bioimpedance spectroscopy to detect sub-clinical lymphedema.Concerning education, we use a 3-pronged approach with surgeons, nurse practitioners, and video representation for patients. We have had 212 patients undergo the ARM procedure since 2019, with three (1.41%) developing persistent lymphedema.Our study underscores the significance of a comprehensive lymphedema prevention program, integrating smarter axillary surgery, early detection, and patient education. The lymphedema rate of 1.41% not only validates the success rate of these interventions but also advocates for their widespread adoption to enhance the holistic care of breast cancer survivors.As we continue to refine and expand our program, further research, and long-term follow-up are crucial to improve prevention strategies continually and enhance the overall well-being of individuals at risk of BCRL.